(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
Clinoptilolite is used as an adsorbent to remove heavy metal cations due to its function as a molecular sieve. This molecular sieve characteristic has made it possible to study the efficiency of clinoptilolite and D-Penicillamine in a comparative way in terms of the adsorption of heavy metals (especially copper) from a biological medium. For this purpose, clinoptilolite was subjected to grinding to produce a homogenized micronized powder in two sizes with d90=75 and 150 μm. Then, initial adsorption tests in an aqueous medium were performed on 10 ppm solutions of iron, zinc, copper, cadmium and nickel cations in single cation solutions, as well as a mixture of cations. In the next step, tests were performed to evaluate the adsorption of Cu2+ on clinoptilolite under different conditions. Experiments have been performed to investigate the effect of pH, temperature (T), adsorbent dosage, time and cation concentration in a simulated biological medium. According to the results, clinoptilolite has a high ability to remove metal cations from aqueous solutions. The 99.71% removal of copper cations by clinoptilolite indicates the high ability of this mineral to remove copper from any environment. In a simulated biological medium at pH=7 and 5, the copper adsorption rate was 98.18 % and 97.45 % respectively, which indicates the high ability of zeolite to absorb copper cations under biological conditions. An examination of the mass balance calculations has also shown the ability to replace clinoptilolite with penicillamine; 15 mg of clinoptilolite removes 214 mg of Cu from aqueous solutions, which is equivalent to the formation of copper-penicillamine chelate.